A Space Syntax Guide to Optimize Shopping Mall: A Systematic Review - Andi Andi; Ivan Adiel Abednego; Bontor Jumaylinda Br. Gultom (International Journal of Environment, Architecture, and Societies, 2021)
The shopping mall is a facility for profit-making with a complex spatial configuration that prioritizes the effectiveness in any aspects. The spatial configuration of a shopping mall needs more than a rule of thumb or a subjective judgment to optimize it. Many researchers have conducted studies of shopping mall spatial configuration by the theory and method of space syntax. But, the complexity of space syntax turns it hard to understand or apply in practical use. Due to the complexity of both shopping mall and space syntax, a guide is needed for practical directions to optimize shopping mall. This article review combines and synthesizes the findings of space syntax precedent studies. The scope of the study is on the building configuration scale (mesoscale). As the result, the optimization of a shopping mall can be measure by space syntax through measurement of connectivity, depth, integration, choice, and intelligibility. Each measurement has a different purpose. The most used measurement in shopping mall study is integration. The spatial configuration of the mall can be represented by the axial map, convex map, isovist map, VGA map, and agent-based in space syntax analyses. The most suitable map for shopping mall analysis is the VGA map because it shows the visual quality is vital in shopping mall design. There are several aspects of the shopping mall that can be adjusted or modified to optimize the shopping mall. Those aspects are pedestrian flows, horizontal complexity, vertical complexity, tenant type allocation, visual quality, retail placement, and anchor placement.